Measurement of Muon Neutrino Quasielastic Scattering on Carbon - Aguilar-Arevalo, A. A.; Bazarko, A. O.; Brice, S. J.; Brown, B. C.; Bugel, L.; Cao, J.; Coney, L.; Conrad, J. M.; Cox, D. C.; Curioni, A.; Djurcic, Z.; Finley, D. A.; et al. (Physical review letters, 2008)
The observation of neutrino oscillations is clear evidence for physics beyond the standard model. To make precise measurements of this phenomenon, neutrino oscillation experiments, including MiniBooNE, require an accurate description of neutrino charged current quasielastic (CCQE) cross sections to predict signal samples. Using a high-statistics sample of nu_(mu) CCQE events, MiniBooNE finds that a simple Fermi gas model, with appropriate adjustments, accurately characterizes the CCQE events observed in a carbon-based detector. The extracted parameters include an effective axial mass, M_(A)(eff)=1.23+/-0.20 GeV, that describes the four-momentum dependence of the axial-vector form factor of the nucleon, and a Pauli-suppression parameter, kappa=1.019+/-0.011. Such a modified Fermi gas model may also be used by future accelerator-based experiments measuring neutrino oscillations on nuclear targets.